On Peace and Insurgency: President Estrada and the Conflict in Mindanao - Honasan, Gregorio B. (Kasarinlan: Philippine Journal of Third World Studies; Vol 15 No 2 (2000): Indigenous Peoples, 2009)
More than the average politician, renegade soldier-turned lawmaker Senator Gregorio Honasan understands President Joseph Estrada's order to use force against the Moro International Liberation Front (MILF) rebels. He believes the Estrada government had very little choice as the presence of the MILF secessionist camps in Mindanao was an affront to national sovereignty that no self-respecting government would have tolerated. Honasan stresses that the conflict, which has inflicted upon the nation billions in losses and an incalculable cost of human lives, must end and that the present administration has an opportunity to do so soon. Once the Mindanao conflict is resolved, the region may finally catch up with the rest of the country through Senator Honasan's proposed Mindanao Initiative. Patterned after the Marshall Plan of 1947, the proposed legislation would provide for the rebuilding of the Muslim communities long neglected by the central government. The Plan aims to provide emergency relief assistance, rehabilitate damaged social infrastructure and accelerate the implementation of development programs. Also among its goals are the increased transfer of real resources to Mindanao and the closer monitoring of government projects in Mindanao. Aside from the implementation of the Plan, there is also an urgent need for a stronger political representation for Muslims in Manila. Meanwhile, the government and the MILF should refrain from imposing deadlines and ultimatums and instead find patience in the slow moving path toward peace.
Keywords: Estrada; Erap; War; MILF